Pulmonary function and anthropometric characteristics in elite triathletes - Alonso-Calvete, A.; Gonzalaez-Gonzalez, Y.; da Cuna-Carrera, I. (Journal of Physical Education and Sport, 2020)
Problem statement: Pulmonary function and anthropometric characteristics influence athletes' performance and development during their trainings and also during their competitions. Approach: Duathlon and long-distance triathlon are endurance sports where athletes must perform disciplines like swimming, cycling and running over various distances. The relationship between pulmonary function and anthropometric characteristics is remarkable in triathlon, and gender seems to play an important role in this relationship as it has been demonstrated by many authors. Purpose: The purpose of this study was to analyse the differences in pulmonary function among athletes from duathlon and long-distance triathlon, taking gender into consideration, and to determine the relationship between pulmonary function and anthropometric characteristics in this sport. Results: 33 athletes (11 subjects from long-distance triathlon and 22 subjects from duathlon) were recruited for this study. Height and weight were measured, and spirometry was performed 3 times in order to test pulmonary function parameters. The pulmonary function data analysed were forced vital capacity, forced expiratory volume during the first second and peak of expiratory flow. The only statistically significant difference between duathletes and long-distance triathletes was observed in the peak of expiratory flow, and there were no differences between genders. Body mass index is only correlated with forced vital capacity in subjects who performed long-distance triathlon, and height is correlated with all the pulmonary function data in duathlon. Conclusion: Long-distance triathlon athletes have significant higher levels of the peak of expiratory flow than duathletes in this sample. Gender does not play an important role in pulmonary function parameters, but it does in anthropometric characteristics for both sports.